The audio-described screenplay of the Argentinean film El secreto de sus ojos (Juan José Campanella, 2009): from images to words - Cabezón Doty, Claudia (2023)
This article, framed within the field of intermedial relations, audiovisual translation studies and transatlantic studies, aims to propose a new type of reciprocity and permeability between cinema and literature by analysing the audio-described version of the Argentinean film El secreto de sus ojos (Juan José Campanella, 2009) from the following perspective: audio-description as an example of intersemiotic translation (from images to words), subordinate (to iconic codes) and accessible. In this context, the aim is to highlight the reception and perception of a new group of viewers, namely blind and visually impaired people, by investigating the intralinguistic audio-described version produced in Argentina by the Ci Rosario Audio Description Group. This brief study will also compare the styles and quality criteria of audio description in cinema both in Europe (Germany and Spain) and in Latin America (Argentina).